Peningkatan Kemampuan Matematika Anak Usia Dini Melalui Permainan Jam Pintar di Taman Kanak - Kanak Pembina Kec. Bangkinang Kota - Mohammad Fauziddin (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2015)
The research problem is the lack of children's ability to recognize the concept of numbers, the child can only mention the numbers in sequence. The purpose of research is to improve math skills early childhood through clever game clock and method of the research is mixed method of qualitative and quantitative as well as the type of research is a classroom action research. The results of each cycle research shows the increase of mathematical abilities of children, ranging from the first cycle is generally still low after the action on the second cycle increased.